Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Spatiotemporal variations and influencing factors of the incidence of cervical and breast cancer among rural women in Anhui Province, China - Xiaoqing Song; Yi Lu; Rong Wang; Jian Mao; Yi Long; Wei Jiang; Jingwen Hu (Applied Geography, 2026)

Investigation of In-Situ Shear Failure Mechanism of Rock and Acoustic Emission Characteristics Using Discrete Element Method - Long Chen; Jian-jun Huang; Ze Yang; Shun-chuan Wu; Shang-rong Wu; Yu-song Zhao (Applied Geophysics, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

An intelligent nanotheranostic for size-driven integrated tumor radiosensitization and radioprotection - Mengting Gao; Yarong Jin; Xiaorui Song; Jian Zhang; Ajing Wu; Qiao Ye; Binyue Zhang; Jinxuan Li; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Temporal dynamics and task-dependent neural mechanisms in facial symmetry processing - Jian Wang; Rong Cao; Song Xue (Experimental Brain Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Effective periodate activation of direct Z-scheme g-C3N4/Cu2O heterojunction for photocatalytic norfloxacin degradation, anti-bacterial activity and toxicity assessment - Qinyi Gu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Ziyao Zhou; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2025)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Constructing direct Z-scheme heterojunction of NiCo-LDH coated with g-C3N4 for boosting photocatalytic H2 evolution - Qinyi Gu; Chujun Feng; Congtian Liu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Zhongyu Li; Song Xu (Fuel, 2024)

A twin S-scheme CoFe2O4/VCNDA/BiVO4 nanozyme for photo-auto-enzyme-coupled catalytic degradation of carbamazepine - Chujun Feng; Qinyi Gu; Jian Rong; Xudong Zheng; Yuzhe Zhang; Qian Liang; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)